Analysis of teacher organization commitment in Tangerang Regency public junior high school - Huda, Syafa'at Ariful; Jaenudin, Jaenudin; Iriansyah, Herinto Sidik (Intelektual Pustaka Media Utama, 2024)
This study analyzes the influence of locus of control and supervision channelled to an organization as a whole on organizational commitment and examines and describes the influence of locus of control and supervision on organizational commitment. The instrument uses questionnaires. The sample is determined by proportional stratified random sampling. From 268 teacher samples from 33 public junior high schools in Tangerang Regency, data analysis used structural equation modeling (SEM). The findings show that locus of control and supervision significantly affect organizational commitment, and locus of control significantly affects supervision. These findings prove that the locus of control and supervision of teachers can act as indicators of organizational commitment. The practical implication of this research is to provide knowledge and information for teachers and school management to increase organizational commitment by applying the concepts of locus of control and teacher supervision.